Venous Thromboembolism as an Adverse Effect During Treatment With Olanzapine: A Case Series - Masopust, Jiri; Bazantova, Vera; Kuca, Kamil; Klimova, Blanka; Valis, Martin (Frontiers in Psychiatry, 2019)
Objective: Venous thromboembolism (VTE) is a serious multifactorial disorder. Patients with severe mental illness have a higher risk of developing the condition compared to the general population. Methods: We observed ten cases of VTE in patients with mental illness who were treated with the antipsychotic drug olanzapine. The diagnosis of VTE was made at the University Hospital Hradec Kralove (UH HK) from 2004 to 2013. VTE was objectively determined by imaging techniques (duplex ultrasonography, CT angiography) and laboratory tests (D-dimer). The average age was 46 years. The clinical manifestation of VTE was deep vein thrombosis in 9 cases, including one case of simultaneous pulmonary embolism and one case of a concurrent ischaemic cerebrovascular accident (iCVA). None of our patients had a history of malignant disease, trauma or surgery. Results: Apart from antipsychotic medication, all the patients had clinical or laboratory risk factors for VTE. The most frequent clinical risk factors were obesity (n = 7) and smoking (n = 6). The most frequent laboratory risk factors were increased levels of F VIII (n = 4), mild hyperhomocysteinemia (n = 3) and factor V Leiden mutation (n = 2). VTE developed within 3 months after antipsychotic drug initiation in three patients and within 6 months in three patients. Conclusion: Olanzapine can be considered a precipitating factor for VTE formation. When olanzapine is administered, we need to monitor for clinical signs and symptoms of VTE, especially when other risk factors are present.